2014
DOI: 10.1097/mpg.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wheat Bran Extract Containing Arabinoxylan Oligosaccharides on Gastrointestinal Parameters in Healthy Preadolescent Children

Abstract: WBE is well tolerated at doses up to 5 g/day in healthy preadolescent children. In addition, the intake of 5 g/day exerts beneficial effects on gut parameters, in particular an increase in fecal bifidobacteria levels relative to total fecal microbiota, and reduction of colonic protein fermentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…Other non-digestible carbohydrates, such as resistant starch and whole grain barley, appear to also increase abundance of Ruminococcus , E. rectale , and Roseburia [3, 67, 68]. Additionally, FOS-, polydextrose-, and AOS-based prebiotics have been observed to reduce Clostridium [6972] and Enterococcus species [7376]. A cross-sectional study of 344 patients with advanced colorectal adenomas revealed that Roseburia and Eubacterium were significantly less prevalent, while Enterococcus and Streptococcus were more prevalent in these subjects compared to healthy controls.…”
Section: Diet and Microbiotamentioning
confidence: 99%
“…Other non-digestible carbohydrates, such as resistant starch and whole grain barley, appear to also increase abundance of Ruminococcus , E. rectale , and Roseburia [3, 67, 68]. Additionally, FOS-, polydextrose-, and AOS-based prebiotics have been observed to reduce Clostridium [6972] and Enterococcus species [7376]. A cross-sectional study of 344 patients with advanced colorectal adenomas revealed that Roseburia and Eubacterium were significantly less prevalent, while Enterococcus and Streptococcus were more prevalent in these subjects compared to healthy controls.…”
Section: Diet and Microbiotamentioning
confidence: 99%
“…[16][17][18] Short-term human studies with the novel prebiotic arabinoxylan-oligosaccharides (AXOS) derived from wheat bran have been reported to increased Bifidobacterium abundance and improve postprandial glycemia. [19][20][21][22][23] Further, AXOS intervention softened stool consistency and increased stool frequency in some, [23][24][25] but not all short-term human interventions. 20,22 Yet it is unknown how AXOS affects gastrointestinal transit and metabolic health in the long-term.…”
Section: Introductionmentioning
confidence: 98%
“…AXOS are non-digestible, fermentable prebiotic oligosaccharides, of which the bifidogenic activity has been demonstrated in vitro ( 5 ) , in animals ( 6 , 7 ) , in healthy adults ( 8 10 ) and in healthy children ( 11 ) . Next to bifidogenic activity, AXOS have been shown to increase the faecal levels of acetic acid, propionic acid and butyric acid ( 10 ) , in turn leading to acidification of the colonic lumen.…”
mentioning
confidence: 99%